VALES – III. The calibration between the dust continuum and interstellar gas content of star-forming galaxies. (27th February 2017) - Hughes, T. M.; Ibar, E.; Villanueva, V.; Aravena, M.; Baes, M.; Bourne, N.; Cooray, A.; Davies, L. J. M.; Driver, S.; Dunne, L.; Dye, S.; Eales, S.; et al.
Abstract: We present the calibration between the dust continuum luminosity and interstellar gas content obtained from the Valparaíso ALMA Line Emission Survey (VALES) sample of 67 main-sequence star-forming galaxies at 0.02 < z < 0.35. We use CO(1–0) observations from the Atacama Large Millimetre/submillimetre Array to trace the molecular gas mass, M H 2, and estimate the rest-frame monochromatic luminosity at 850 μm, $L_{ν _{850}}$, by extrapolating the dust continuum from magphys modelling of the far-ultraviolet to submillimetre spectral energy distribution sampled by the Galaxy And Mass Assembly survey. Adopting αCO = 6.5 (K km s −1 pc 2 ) −1, the average ratio of $L_{ν _{850}}$ / M H 2 = (6.4 ± 1.4)× 10 19 erg s −1 Hz −1 M$_{{\odot }}^{-1}$, in excellent agreement with literature values. We obtain a linear fit of $\log _{10} \left(M_{H_{2}}/{M_{{\odot }}}\right) = (0.92± 0.02) \log _{10} (L_{ν _{850}}/{erg\, s^{-1}\, Hz^{-1}})-(17.31± 0.59)$ . We provide relations between $L_{ν _{850}}$, M H 2 and M ISM when combining the VALES and literature samples, and adopting a Galactic αCO value.